Sanitation and Physical Quality of Water Refilled Drinking Water Depot in the Working Area of Kotaraja Puskesmas - Nita; Hasmi; Medyati, Novita; Zainuri, Agus; Makaba, Sarce; Togodly, Arius (PT FORMOSA CENDEKIA GLOBAL, 2024)
Data on the sanitation quality of refill drinking water depots in the Kotaraja Community Health Center working area is 30% not meeting the physical feasibility requirements. The research aims to determine the sanitation and physical quality of refilled drinking water in the Kotaraja Community Health Center Working Area. Type of quantitative descriptive research. The population is 36 drinking water depots. Data measurement uses an observation sheet instrument. The research results were obtained from sanitary conditions of the 36 refill drinking water depots in the Kotaraja Community Health Center working area where 11 depots (30.6%) did not meet the requirements and 25 depots (69.4%) met the criteria. Equipment sanitation 4 depots (11.1%), does not meet the requirements and meets the requirements of 32 depots (88.9%). Physical quality of drinking water from the results of equipment sanitation and processing there are 7 depots (19.4%) do not meet the requirements 29 depots (80.6%) met the criteria